Results of the use of silodosin in acute urinary retention caused by Benign prostatic hyperplasia (Progress Annals: Journal of Progressive Research, 2023)
The article provides .α-blockers are widely used to treat one of the most serious complications of benign prostatic hyperplasia (BPH), acute urinary retention (AUR). Experience with the use of a new uroselective α-adrenergic blocker, silodosin, approved for the treatment of patients with urinary disorders caused by BPH, is presented. Its pharmacological profile has a number of advantages, including the highest uroselectivity to date, rapid onset of effect, the ability to take a standard dose of 8 mg once a day, which does not require adjustment depending on age; possibility of simultaneous use with antihypertensive drugs.